Designing the Sentence Box as A Medium for Teaching the Simple Present to the Tenth Graders - Fauziyah, Nailul (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
The innovation of teaching media is very important to help students’ enhancement in learning English grammar, especially the simple present. The tenth graders students of SMA X need something different to make them enjoy and be interested while learning the simple present. This study was conducted to design a teaching medium for teaching the simple present to the tenth graders. The research model used in this study was design-based research of Hannafin and Pack’s Theory in Isman et al., (2005) there were three phases; the first phase was needs analysis. Based on the teacher’s interview and students’ questionnaire, the result was as follows; the students had never used physical teaching media such as flashcards and the teacher used a handbook or module. Followed by the design phase, the first medium validation got some suggestions from an expert by changing the words in each sentence. The last phase was media implementation, the students were asked to assess the medium by filling out the responses’ questionnaire. The result showed that they gave positive responses, felt helpful, and enjoyed while playing Sentence Box. This teaching medium would be appropriate for teaching grammar especially the simple present tense, interesting, innovative, also the procedures are clear and understandable.